Geronimo Stilton reporter. 20, Starring Geronimo - Stilton, Geronimo; Costa, Davide (Stilton, Geronimo. Geronimo Stilton reporter, 2025)
"When the New Mouse Playhouse struggles to keep afloat, Geronimo agrees to write an article on their most recent show. But strange events that occur in the vicinity of the theater threaten the production. Sally Ratmousen is after a secret room in the New Mouse Playhouse and will use every dirty trick in the book to have it close down to grant them free access, even sabotage the next production. However, the Stiltons are on the case and may get in on the secret to help save the day."--Publisher.